Hybrid Educational Chatbot Integrating AIML 2.0 and Ontology-Based Reasoning for Intelligent Tutoring (International Journal of Scientific Research in Science and Technology, 2025)
This paper presents an enhanced design for an educational chatbot that combines the AIML-based CHARLIE system with the advancements found in AIML 2.0 and ChatScript. The system improves natural language interaction, supports dynamic learning, integrates ontologies, and ensures mobile compatibility. The goal is to create a flexible, intelligent assistant for learning platforms.